Acoustic parameters of sound insulating materials investigation in small reverberation rooms on rubber plates - Козлітін, О.О.; Макаренко, В.М.; Плохіх, Л.Г. (Proceedings of National Aviation University (archive), 2005)
The new method of sound insulating materials acoustic characteristics investigation in small reverberation rooms was elaborated. The research of sound insulating materials on rubber plates was done. The analysis of obtained results of acoustic parameters of materials being a part of the composite real structures of airplane was carried out.